2005
DOI: 10.1159/000086931
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Prescribing Practices: A Challenge to Malaria Control in Ghana

Abstract: Objective: The study was conducted to determine antimalarial prescribing practices among prescribers in 2 of the 6 sentinel sites established to document antimalarial drug efficacy in Ghana in order to provide some explanation underlying chloroquine treatment failures in the country. Subjects andMethods: The study was descriptive combining both qualitative and quantitative designs. The qualitative design involved in-depth interviews of general prescribers in the Wassa West and Kassena Nankana districts using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
7
18
1
Order By: Relevance
“…The average number per encounter obtained in this study is comparable to that of a study conducted in Tanzania, where the average number of drugs per encounter was 2.4 [24]. The average number obtained in this study suggests minimal polypharmacy and a specific malaria treatment regimen [23]. However, since this study did not examine whether there was laboratory or rapid diagnostic testing to support treatment with antimalarial drugs, we cannot confirm the latter suggestion.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The average number per encounter obtained in this study is comparable to that of a study conducted in Tanzania, where the average number of drugs per encounter was 2.4 [24]. The average number obtained in this study suggests minimal polypharmacy and a specific malaria treatment regimen [23]. However, since this study did not examine whether there was laboratory or rapid diagnostic testing to support treatment with antimalarial drugs, we cannot confirm the latter suggestion.…”
Section: Discussioncontrasting
confidence: 52%
“…Also, drugs prescribed per encounter were significantly lower than those observed in a similar study within two districts in Ghana, Wassa West and Kassena Nankana. Drugs prescribed per encounter in the latter study were 4.3 and 3.0, respectively, in the two districts [23], and it is worth noting that the studies conducted were undertaken before the introduction of the ACT policy. The average number per encounter obtained in this study is comparable to that of a study conducted in Tanzania, where the average number of drugs per encounter was 2.4 [24].…”
Section: Discussionmentioning
confidence: 79%
“…Irrational prescribing practices, unavailability of drugs, lack of awareness and adherence of prescribers regarding standard treatment guidelines, self medication and overuse of antibiotics were highlighted as the major factors contributing towards irrational drug use in malaria in Pakistan by the respondents. Similar patterns of irrational drug use in other countries have been reported [16][17].…”
Section: Discussionsupporting
confidence: 85%
“…Several studies conducted in Pakistan have reported a more prevalent resistance of falciparum malaria to chloroquine; the use of artimisinin derivatives is more effective but too costly for a developing country to be used on large scale (Shah et al, 1997, Rana, 2004#257, Fox et al, 1985, Ejaz et al, 2007. Similar patterns of irrational drug use have been reported in Ghana and Cambodia (Chareonkul et al, 2002;Abuakua et al, 2005).…”
Section: Discussionsupporting
confidence: 74%